Pulmonary vein antral isolation causes depolarization of vein sleeves: Implications for the assessment of isolation. Issue 2 (11th January 2020) - Saluja, Deepak; Pagan, Eric; Maglione, Theodore; Kassotis, John; Kostis, William J.; Coromilas, James
Abstract: Purpose: Pulmonary vein isolation (PVI) for atrial fibrillation has been shown to result in inexcitability of a large fraction of pulmonary veins (PVs), but the mechanism is unknown. We investigated the mechanism of PV inexcitability by assessing the effects of PVI on the electrophysiology of PV sleeves. Methods: Patients undergoing first‐time radiofrequency PVI were studied. Capture threshold, effective refractory period (ERP), and excitability were measured in PVs and the left atrial appendage (LAA) before and after ablation. Adenosine was used to assess both transient reconnection and transient venous re‐excitability. Results: We assessed 248 veins among 67 patients. Mean PV ERP (249.7 ± 54.0 ms) and capture threshold (1.4 ± 1.6 mA) increased to 300.5 ± 67.1 and 5.7 ± 5.6 mA, respectively ( P  < .0001 for both) in the 26.9% PVs that remained excitable, but no change was noted in either measure in the LAA. In 16.3% of the 73.1% inexcitable veins, transient PV re‐excitability (as opposed to reconnection) was seen with adenosine administration. Conclusions: Antral PVI causes inexcitability in a majority of the PVs, which can transiently be restored in some with adenosine. Among PVs that remain excitable, ERP and capture threshold increase significantly. These data imply resting membrane potential depolarization of the of PV myocardial sleeves. As PV inexcitability hampers the assessment of entrance and exit block, demonstrating transient PV re‐excitability during adenosine administration helps ensure true isolation.